Strategi Penerapan Manajemen kearsipan dalam Mendukung Mutu Pendidikan: Studi Komparasi di IAIN Palangka Raya dan IAIN Syekh Nurjati Cirebon - Puspita, Puspita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Achieving good educational goals cannot be separated from the effectiveness of educational institutions in improving the quality of records management. However, in archive management there is often an increase in the number of archives, while archive storage space is limited. Therefore, appropriate strategies are needed for archive management to support the quality of education through archive management. This study uses a qualitative approach with comparative methods. The objects being compared are institutional and archival management at IAIN Palangka Raya and IAIN Syekh Nurjati Cirebon. The review is carried out through analysis in order to find similarities and differences in phenomena in factors that may be causes through the data. The selection of the IAIN Palangka Raya and IAIN Syekh Nurjati Cirebon Archives was reviewed because the archives are under the Ministry of Religion and are one of the best archives on the island of Kalimantan and Java. This study reveals that based on the results of a review of archives management in educational institutions, namely IAIN Palangka Raya and IAIN Syekh Nurjati Cirebon, they can improve service quality as a strategy. These results can be seen from the analysis using the SWOT method that has been carried out. This comparative study has been carried out on preparedness management in supporting the quality of education at IAIN Palangka Raya and IAIN Syekh Nurjati Cirebon. This can be seen from the role of archives management through planning, organizing, implementing and supervising. Apart from that, through a SWOT analysis of IAIN Palangka Raya and IAIN Syekh Nurjati describes solutions and is oriented towards archives management both in organizational, institutional contexts and in the treatment of governance and accountability. The study findings explain that implementing archives management through SWOT analysis can improve the quality of education. Because archives management can provide archival services by making efforts to collect and manage records. Then, archival services can be maximized with archival functions to provide the required document archives. So that ease of archive management can be achieved because you can easily find and open old archives when they are needed.